A Challenge for Teachers of Inclusive Higher Education - ChÃƒÂ¡vez, Sandra Auxiliadora Romero; Quijije, Karen Katherine Bowen (International Research Journal of Management, IT & Social Sciences, 2018)
The paper shows the results of a research process that aimed to analyze the pedagogical strategies applied by teachers in the academic process to students with disabilities at the Technical University of ManabÃ, thus raising the challenge of training professionals in Higher Education. For this purpose, a qualitative-quantitative methodology was used in which 50 teachers were surveyed, which allowed obtaining the required information. The paper presents the ideas offered by teachers about inclusive education, which leads the institution to reflect to refine strategies that promote management in an inclusive education system. Through the development of the research, it was possible to verify the disposition of the teaching staff of the Technical University of Manabi, to continue reinforcing the inclusive policy drawn up by the government and particularly by the direction of the educational institution.